PENINGKATAN HASIL BELAJAR MENULIS TEKS REPORT MELALUI MODEL PEMBELAJARAN ROUND TABLE SISWA SMP NEGERI 2 DONGKO - TRENGGALEK - Sapto Endah Wahyuni (Education Journal : Journal Educational Research and Development, 2018)
The students’ writing achievement of SMP Negeri 2 Dongko, class IX D especially is low. It can be seen on the mark of students’ assesment on writing Report text. That’s why the research is held as the attempt to find the propper learning model by implementing Round Table model. Hopefully, it is intended to enhance the students’ ability on writing skill. In this case the primary purpose is that the students can explore his idea to compose a good report text. In implementing the Round Table model, the first step is to divide class into small groups consist of 5 students, then In each group the students have to write in turn, a sentence for each, based on the framework they have made before. The research held is Classroom Action Research with the goal to know whether the increasing of the students’ achievement after implementing Round Table model. After the research, the data analized shows that classical learning mastery has increased from 59,46 in pre cycle, 67,89 in cycle 1 and 75,46 in cycle 2. The percentage of learning mastery is also increasing from 57,14% in pre cycle, 71,43% in cycle 1 and 88,57% in cycle 2. Thus, it can be concluded that the implementation of Round Table model has succeded in increasing the achievement on writting Report Text of the IX D students.